EFFECT OF THERMAl POllUTION ON THE HYDROlOGICAl PARAMETERS OF RIVER JHELUM (J & K) - Qureshi, T. A. (Journal of Indian Fisheries Association, 2008)
The Buniyar hydroelectric project and the lower Jhelum Barrier at Gantamulla constructed across river Jhelum are in operation from several years. The two power stations have changed the hydrological features of the area where dam is situated. Therefore, the impact of hydroelectric projects on fishery resources of river Jhelum is a matter of great concern. The treated water from the power house is released through turbines, having cooling effect on them. The change in the hydrological parameters such as increase in temperature, depletion of oxygen etc. might have brought fishes under stress which is the main cause in decreased population of finfishes from site to site. The golden Mahseer, Tor putitora which was once an abundant species in River Jhelum has disappeared due to human intervention. The prevailing water quality around hydroelectric projects is unsuitable for finfishes of river Jhelum. Keywords: Hydroelectric projects, Hydrological Parameters, River Jhelum.